2002
DOI: 10.1046/j.1365-2125.2002.t01-3-01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions and off-label drug use in paediatric outpatients

Abstract: Our data suggest an increasing risk of adverse drug reactions related to off-label drug use. This risk would be acceptable if further studies prove the potential benefit of such a drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
192
1
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(211 citation statements)
references
References 27 publications
5
192
1
12
Order By: Relevance
“…However, administration of a drug outside the conditions assessed during clinical trials may result in adverse drug reactions (ADRs). [1][2][3] Moreover, the specificity of children's physiology and pharmacology should not be neglected. 4 For years, the lack of drug evaluation in children has been evoked as a factor favoring off-label prescribing.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, administration of a drug outside the conditions assessed during clinical trials may result in adverse drug reactions (ADRs). [1][2][3] Moreover, the specificity of children's physiology and pharmacology should not be neglected. 4 For years, the lack of drug evaluation in children has been evoked as a factor favoring off-label prescribing.…”
Section: What This Study Addsmentioning
confidence: 99%
“…As a result of these initiatives, it may be hypothesized that prescribers would be more aware of the potential consequences of off-label prescribing, decreasing the prevalence of off-label prescribing and associated risks. 8 A study 2 performed in the early 2000s in France showed that off-label prescribing was highly prevalent (42%) and significantly associated with ADR occurrence. Since this period, in line with the promotion of drug evaluation and the development of new pediatric formulations, the situation is likely to have evolved.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Poor evidence for safe and effective drug use in paediatric patients represents a clinical burden. In fact, 70 % of prescribed medications are estimated to be off-label, laying patients open to a high risk of adverse effects [2][3][4]. Isn't this an ethical issue too?…”
Section: Dear Editormentioning
confidence: 99%
“…Ces affirmations s'appuient en partie sur l'idée que si une indication n'a pas pu être développée chez les enfants pour ces médicaments, cela a eu pour résultat que des médicaments non conformes mais potentiellement bénéfiques ne sont pas commercialisés alors que d'autres médicaments non conformes et potentiellement dangereux sont prescrits. Bien qu'il y ait sans doute une part de vérité dans cette conception de la chose (voir ci-dessous), 5 les anesthésiologistes pédiatriques ont endossé la responsabilité de mener des recherches et de publier de nombreuses études dans le but d'établir des directives pour un dosage sécuritaire de plusieurs médica-ments non conformes qui sont aujourd'hui considérés 84 CANADIAN JOURNAL OF ANESTHESIA A Terme utilisé pour décrire un médicament qui n'est pas approuvé soit pour l'indication pour lequel il a été prescrit/recommandé et/ou pour l'âge du patient.…”
unclassified
“…The basis for these claims, in part, rests with the notion that the failure to develop a pediatric indication for these drugs has resulted in potentially beneficial off-label drugs being withheld while potentially harmful off-label drugs are prescribed. While there is arguably some truth to the notion (see below), 5 pediatric anesthesiologists have assumed the burden of responsibility in this case investigating and publishing many studies to establish safe dosing guidelines for many off-label drugs that are now considered standard of care in infants and children. For example, the local anesthetic, bupivacaine, is not approved for epidural use in children less than 12 yr of age but based on independent studies in neonates, infants and children, dosing regimens for both single-dose and continuous infusions are both widely and safely practiced today.…”
mentioning
confidence: 99%